INNOVATIVE STRATEGIES IN PEDAGOGY, TRANSLATION THEORY, AND FOREIGN LANGUAGE TEACHING WITHIN THE CONTEXT OF EDUCATIONAL REFORMS IN THE REPUBLIC OF UZBEKISTAN - Azatova Shakhzada; Muratova Dilorom Mahmudovna (TADQIQOTLAR, 2025)
Annotation: This article examines contemporary approaches to linguistic education and translator training amidst widespread digitalization. Special attention is paid to the implementation of state programs in the Republic of Uzbekistan, the introduction of blended learning technologies (Blended Learning), the use of CAT tools, and the CLIL methodology. The paper also analyzes the transformation of the roles of the teacher and the translator within the new educational paradigm.